Akok Gebu Sdn. Bhd. / Norazreen Mat Raius, Norfarahana Jasmin Hassan Basri … [et al.] - MAT RAIUS, NORAZREEN; HASSAN BASRI, NORFARAHANA JASMIN; PEET, SHAHROLNIZAM; ABDULLAH, SITI HARLIZA; ISMAIL @ MUSTAPHA, SITI SHARIFAH NUR; MOHD RADZI, MUNIRAH (2019)
Akok Gebu Sdn. Bhd. is based on partnership where it consists of six members who hold important positions in the company such as General Manager, Administration Manager,Marketing Manager, Assistant Marketing, Operational Manager and Financial Manager. The business capital is amounted to RM250,000 where the total contribution of each member is RM30.000 and acquiring another RM70.000 is from bank loan. Akok Gebu with tagline Taste a Moments" is located at Section 7 Shah Alam. The advantages of our location spot are due to astrategic place because it's near and easy to get supplier for our office equipment and the target customers are there. Besides, the price for the akok is reasonable and affordable.Akok Gebu is a company which focuses on food production in Malaysia. Akok is one of Malay traditional cake and mostly popular in Pantai Timur. Difference in flavors make this cake looks interesting and suitable to serve for any occasion. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. To make it more attractive and interesting, we decided to make some innovation by implying our creativity and modern element in this akok making. Nowadays, color and flavor is one of the important thing in any products making so colorful of akok with flavor might be a new attraction to people.We have done some research that Malaysia is one of developed country and it quite busy during day time. Normally people who work during office hour and students do not have much time for breakfast. So, with our new innovation, they can just grab a packet of akok with different fillings and go to work. Easy and simple as that. Our business is expected to commence on January 2020 and our vision is to make our company a well-known, established and satisfied by our customer in order to expand our akok to attract other bakeries company to deal with us with a better price. We also hope that our company can produce the profit within 3years. This will be realized by the full cooperation and efforts among the partners to promote the company.